Successful Management of a Catecholamine-Secreting Glomus Jugulare Tumor with Radiosurgery Alone - Fussey, Jonathan M.; Kemeny, Andras A.; Sankar, Sailesh; Rejali, Darius (Journal of Neurological Surgery Part B: Skull Base, 2013)
Secretory glomus jugulare tumors are often resected surgically to control the systemic effects of the catecholamines they produce. This involves complex skull base surgery, which carries significant risks and frequent morbidity. Stereotactic radiosurgery (SRS) is a recently recognized treatment for glomus jugulare tumors, though little is known about its use in secretory tumors.Case Report A young fit patient with a catecholamine-secreting glomus jugulare tumor was treated with SRS alone and over the following 37 months her urinary catecholamine excretion fell to near normal levels, and serial magnetic resonance imaging (MRI) confirmed a reduction in tumor volume.Discussion Radiosurgery is an accepted treatment for glomus jugulare tumors and is now readily available to skull base surgeons. In this case a catecholamine-secreting tumor was successfully controlled with radiosurgery alone. Further research and long-term follow-up will determine the role of this treatment in the nonsurgical management of secreting glomus jugulare tumors.
Keywords: glomus jugulare; radiosurgery; catecholamines; gamma knife